Transformasi Desa Surabaya Utara Melalui Teknologi Informasi - M Nurul Wathani; Amri, Zaenul; Suhartini; Sanusi, M Ujang; Saputra, Lalu Rendi (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
The low level of digital literacy and minimal use of information technology (IT) remain major obstacles to accelerating development in North Surabaya Village, East Sakra District. This condition causes village administrative services to run less efficiently, and elementary school students are unprepared for digital era challenges, such as the Computer-Based National Assessment (ANBK). This Community Service Activity (PKM) aims to provide solutions through comprehensive IT education and technical training as an initial step toward realizing a digitally literate society. The activity implementation method uses a participatory approach involving needs observation, socialization on the importance of digital transformation, and hands-on training. The target audience includes village officials, the general public, and students of SDN 1 North Surabaya. Training materials are tailored to the target needs, covering basic computer operation, office applications for administration, healthy internet use, and an introduction to digital economic potential. The results of this activity show a significant increase in participants' understanding and skills, where village officials began to operate basic applications to support administration, and students became more confident in using computers as learning media. This activity successfully served as a catalyst for changing the community's mindset from conventional to more adaptive to technology while laying the initial foundation for North Surabaya Village to become an independent digital village